2014
DOI: 10.1590/s0102-71822014000200004
|View full text |Cite
|
Sign up to set email alerts
|

La atribución de responsabilidad: de la cognición al sujeto

Abstract: El estudio de los procesos de responsabilización es especialmente importante para la comprensión del discurso político neoliberal que apela, mediante la paradoja, a valores individuales para afrontar problemas socioestructurales. La adscripción de responsabilidad ha sido tratada en la psicología social en el marco, principalmente, de la teoría de la atribución causal. Aun cuando la propuesta original de Heider es compleja y susceptible de un desarrollo sociológico, el autor opta por un enfoque cognitivo indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
0
2
0
5
Order By: Relevance
“…The outcome has been a widespread collapse of the social in favor of the psychological (Crespo & Freire, 2014), with politics (with a capital P) being gradually replaced by therapeutic politics (with a small p) (McLaughlin, 2010), and with the discourse of personal happiness progressively substituting the discourse of individualism in the definition of the neoliberal model of citizenship (Cabanas, 2013;Cabanas & Huertas, 2014;Cabanas & Sa´nchez-Gonza´lez, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcome has been a widespread collapse of the social in favor of the psychological (Crespo & Freire, 2014), with politics (with a capital P) being gradually replaced by therapeutic politics (with a small p) (McLaughlin, 2010), and with the discourse of personal happiness progressively substituting the discourse of individualism in the definition of the neoliberal model of citizenship (Cabanas, 2013;Cabanas & Huertas, 2014;Cabanas & Sa´nchez-Gonza´lez, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly the turn to happiness makes its appearance right after the consolidation of what authors such as Gilles Lipovetsky (1983) identified as ''the second individualistic revolution,'' a pervasive cultural process of individualization and psychologization which has progressively and deeply transformed the political and social orders of accountability within neoliberal societies (see also Beck & Beck-Gernsheim, 2002), rendering the structural deficits, contradictions, and paradoxes of society in terms of psychological features and individual responsibilities. The outcome has been a widespread collapse of the social in favor of the psychological (Crespo & Freire, 2014), with politics (with a capital P) being gradually replaced by therapeutic politics (with a small p) (McLaughlin, 2010), and with the discourse of personal happiness progressively substituting the discourse of individualism in the definition of the neoliberal model of citizenship (Cabanas, 2013;Cabanas & Huertas, 2014;Cabanas & Sa´nchez-Gonza´lez, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Cada vez que una persona experimenta una emoción, tiene la posibilidad de analizar su origen y atribuirla a estímulos que la hayan activado, los cuales responden al interrogante de por qué se piensa que se ha sentido esa emoción en un momento determinado, de modo que una atribución consiste siempre en una inferencia, así como percibir significa, en todos los casos, una construcción mental (Crespo y Célio, 2014). Por consiguiente, una atribución representa la certeza de los significados que se encuentran asociados a un hecho, de modo que los procesos de atribución de las personas descubren las causas de los sucesos o los comportamientos (Sanz, Menéndez, Rivero y Conde, 2017).…”
Section: Atribución Causal De Las Emocionesunclassified
“…Excluímos aqueles em que a palavra só era citada no resumo ou nas referências. Restaram 18 (Accorssi, Scarparo, & Guareschi, 2012;Batista, Grisci, Gallon, & Figueiredo, 2013;Brussino, Alonso, & Imhoff, 2015;Caniato, 2007;Caniato & Rodrigues, 2012;Chaves & Ribeiro, 2014;Crespo & Freire, 2014;Euzébios & Guzzo, 2009;Fontenelle, 2010;Heilborn & Cabral, 2013;Juárez-Salazar, 2015;Laureano & Peixoto, 2014;Lima & Machado, 2012;Mattos & Ferreira, 2004;Nogueira, 2013;Nunes & Camino, 2011;Roso, Strey, Guareschi, & Bueno, 2002;Xavier, 2002), incluindo artigos do Prêmio ABRAPSO. Isto representa 2,09 % das referências na revista.…”
Section: Produção Científica Em Ideologia: O Que Se Divulga Na Psicolunclassified